A retrospective evaluation of restorations performed at the restorative dental treatment clinic of the dentistry faculty in Adiyaman university - Cellik, Omer (Annals of Medical Research, 2021)
Aim: The study aims to retrospectively evaluate the distribution of the restorations performed at the Restorative Dental Treatment Clinic of the Dentistry Faculty in Adiyaman University between 2016 and 2019 in terms of age, gender and teeth groups. Materials and Methods: In order to examine the distribution of the restorations according to age groups, 5 different age groups were formed as 16-25, 26-35, 36-45, 46-55, and 56 and above. The distribution of the restorations according to teeth groups was evaluated in groups of incisor teeth, premolar teeth and molar teeth. The data obtained were expressed numerically (percentages), and bilateral comparison between the groups were made through Chi-Square (χ2) test. Results: In the study, 9,720 restorations performed on 4,530 patients were examined. 5,951 (59%) of the restorations were performed on females, while 3,769 (41%) of the restorations were applied to male patients. The group that received the most restorations was 16-25 age groups, whereas the least restorations were performed on the age group of 56 and above. When the distribution of the restorations was examined in terms of teeth groups, it was determined that molars were the teeth group which were restored the most, which were followed by incisor teeth group and premolar teeth group, respectively. Conclusion: When the restorations performed at the restorative dentistry were examined in terms of age, gender and teeth groups, it was determined that the need for dental treatment was the most in the young population and females. When it is considered that it was the molar teeth that needed the most treatment, it can be concluded that this situation should be evaluated in the practices of public oral and dental health and preventive dentistry.
Keywords: Age groups; dental caries; gender; molar teeth